Pengaruh Kepemimpinan Transformasional, Motivasi Kerja, Kepuasan Kerja terhadap Kinerja Karyawan PT. Kharisma Pemasaran Bersama Nusantara dengan Komitmen Organisasi sebagai Variabel Mediasi - Pranata, Harry Mulya; Widodo, Slamet (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to identify factors that influence employee performance at PT. Kharisma Pemasaran Bersama Nusantara. A dynamic work environment, transformational leadership is a leadership model that is considered effective in inspiring, motivating and improving employee performance. This model has several characteristics that make it successful in a kinetically changing world of work. This research adopts an explanatory quantitative approach with the variables studied being transformational leadership, work motivation, job satisfaction, organizational commitment and employee performance. The data analysis technique uses path analysis. The results of this research reveal that employee satisfaction influences employee performance with organizational commitment as an intervening variable. Employee satisfaction has a positive effect on employee performance, job satisfaction has an effect on organizational commitment, organizational commitment also has an effect on employee performance at PT. Kharisma Pemasaran Bersama Nusantara.